Thrombin Generation and Cirrhosis: State of the Art and Perspectives - Lebreton, Aurélien; Sinegre, Thomas; Lecompte, Thomas; Talon, Laurie; Abergel, Armand; Lisman, Ton (Seminars in Thrombosis and Hemostasis, 2020)
Epidemiological and laboratory studies performed in the last decades have changed our understanding of coagulopathy in cirrhosis, from a condition at increased risk of hemorrhagic events to one at higher thrombotic risk. However, it is not clear whether the decrease in factors that promote (except factor [F] VIII) versus inhibit coagulation in patients with cirrhosis results in a rebalanced state or in a hypercoagulable phenotype. This issue can be partially addressed using thrombin generation assays (TGA), which unlike routine clotting tests (prothrombin time or activated partial thromboplastin time) are sensitive to both procoagulant factors and coagulation inhibitors. However, many preanalytical issues and variable analytical methodologies used in TGAs complicate data analysis and interlaboratory comparisons. The introduction of TGAs in which activators of the protein C pathway (particularly soluble forms of thrombomodulin [TM]) are added has allowed detection of a reduced anticoagulant effect of TM or even a hypercoagulable phenotype as judged by endogenous thrombin potential. However, inter- and intra-assay variability may be greater with this TGA variant compared with “standard” TGAs. TGAs also allowed identifying main determinants of the hypercoagulability phenotype in the presence of TM: acquired antithrombin and protein C deficiencies, and elevated FVIII levels. The aim of this narrative review is to summarize the preanalytical and methodological variables of TGAs and also the findings of the main studies that have evaluated TGAs in patients with cirrhosis. The review also provides some propositions for future studies and outlines some perspectives on the potential implementation of this promising tool in clinical practice for the study of coagulation in patients with cirrhosis.
Keywords: cirrhosis; coagulation; hemostasis; liver; thrombin generation